2002
DOI: 10.1556/aalim.31.2002.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Working up a lactofermented vegetable product

Abstract: The combination of lactofermentation and enzyme-treatment (Rohament-PL as endo-polygalacturonase and the mixture of Rohament-PL and Rohalase 7069 as cellulase) of sliced carrot and orange juice resulted in a homogeneous product, with pleasant organoleptic features, after 18 h fermentation period. Two ways of inoculation were applied with Lactobacillus plantarum. The addition of Rohament-PL, even at 150 mg kg -1 concentration, simultaneous inoculation with Lactobacillus plantarum (circumstances: 28 °C, 80 r.p.m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Without pasteurization, the total amount of mesophilic aerobes was approximately 10 6 cfu/ml. This number is much higher than the results (3 Â 10 3 cfu/ml) reported by Nagy-Gasztonyi et al [29], but it agrees with the data reported by Song et al [30]. Sulphite-reducing clostridia were below the detection limit (10 2 cfu/ml).…”
Section: Effects Of Heat Treatment On Carrot Juicesupporting
confidence: 89%
“…Without pasteurization, the total amount of mesophilic aerobes was approximately 10 6 cfu/ml. This number is much higher than the results (3 Â 10 3 cfu/ml) reported by Nagy-Gasztonyi et al [29], but it agrees with the data reported by Song et al [30]. Sulphite-reducing clostridia were below the detection limit (10 2 cfu/ml).…”
Section: Effects Of Heat Treatment On Carrot Juicesupporting
confidence: 89%